Pengaruh Fasilitas, Motivasi, dan Kedisiplinan Terhadap Prestasi Belajar MIPA di Sekolah Menengah Atas - Agus Narimo (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The objectives to be achieved in this study are to find out, To find out the influenceof learning facilities at home on the learning achievement of Mathematics and Natural Sciences students of class XI MIPA in SMA Negeri 1 Cawas Klaten Regency. The results showed, there was an influence of learning facilities at home, MIPA learning motivation and learning discipline on the learning achievement of MIPA students in grade XI MIPA in SMA Negeri 1 Cawas Klaten, so that the research hypothesis was accepted. The effective contribution of the influence of learning facilities at home, MIPA learning motivation and learning discipline on the learning achievement of MIPA students in grade XI MIPA in SMA Negeri 1 Cawas Klaten by 54.6% and the remaining 45.4% is influenced by other variables not included in the study this. The effective contribution of MIPA learning motivation to the MIPA students' learning achievement in the XI MIPA grade students in SMA Negeri 1 Cawas Klaten is 21.8% and the relative contribution is 39.9%. Cawas Klaten Regency, so the research hypothesis was accepted. The effective contribution of learning discipline to the learning achievement of Mathematics and Natural Sciences students of class XI MIPA in SMA Negeri 1 Cawas, Klaten Regency was 23.6% and the relative contribution was 43.1%.